Testimonial. Reflections: The Journey of Lausanne Laboratory Lesson Study - Lee, Christine (Formation et pratiques d’enseignement en question, 2026)
This issue marks a significant milestone in the 10-year journey of Lausanne Lesson Study Laboratory (3LS) at the University of teacher education, State of Vaud, Switzerland. It showcases the successful “coming together” among 3LS Lab members, who hail from diverse backgrounds and experiences in teacher education, encompassing both general and subject-specific didactics. Their collective efforts transcend a range of subjects, including mathematics, art and technical disciplines, and history, and span various educational settings, from early childhood education to tertiary education. These efforts encompass initial teacher training, in-service teacher training, and the training of teacher educators and mentors.